Apathy in Frontotemporal Dementia: Behavioral and Neuroimaging Correlates - Eslinger, Paul J. (IOS Press, 2012)
We investigated the occurrence of goal-directed motivational change in the form of apathy in patients with frontotemporal dementia (FTD), particularly those with behavioral variant social and executive deficits (bvFTD). Standardized behavioral inventory was employed to survey and compare apathy ratings from patients and caregivers. In cases of bvFTD, apathy ratings were further related to measures of social cognition, executive function, and atrophy on brain MRI. Results indicated that caregivers rated bvFTD patients as having significantly elevated apathy scores though patient self-ratings were normal. Caregiver and self-ratings of FTD samples with progressive nonfluent aphasia and semantic dementia did not differ from healthy controls and their informants. In the bvFTD sample, caregiver apathy scores were not correlated with general cognitive screening or depression scores, but were significantly correlated with social cognition and executive function measures. Voxel-based morphometry revealed that apathy ratings in bvFTD were related to prominent atrophy in the right caudate (including the ventral striatum), the right temporo-parietal junction, right posterior inferior and middle temporal gyri, and left frontal operculum- anterior insula region. Findings suggest that bvFTD is associated with a significant breakdown in goal-directed motivated behavior involving disruption of cortical-basal ganglia circuits that is also related to social and executive function deficits.